Conservation hotspots for marine turtle nesting in the United States based on coastal development. Issue 8 (13th October 2016) - Fuentes, Mariana M. P. B.; Gredzens, Christian; Bateman, Brooke L.; Boettcher, Ruth; Ceriani, Simona A.; Godfrey, Matthew H.; Helmers, David; Ingram, Dianne K.; Kamrowski, Ruth L.; Pate, Michelle; Pressey, Robert L.; Radeloff, Volker C.
Abstract: Coastal areas provide nesting habitat for marine turtles that is critical for the persistence of their populations. However, many coastal areas are highly affected by coastal development, which affects the reproductive success of marine turtles. Knowing the extent to which nesting areas are exposed to these threats is essential to guide management initiatives. This information is particularly important for coastal areas with both high nesting density and dense human development, a combination that is common in the United States. We assessed the extent to which nesting areas of the loggerhead ( Caretta caretta ), the green ( Chelonia mydas ), the Kemp's ridley ( Lepidochelys kempii ), and leatherback turtles ( Dermochelys coriacea ) in the continental United States are exposed to coastal development and identified conservation hotspots that currently have high reproductive importance and either face high exposure to coastal development (needing intervention), or have low exposure to coastal development, and are good candidates for continued and future protection. Night‐time light, housing, and population density were used as proxies for coastal development and human disturbance. About 81.6% of nesting areas were exposed to housing and human population, and 97.8% were exposed to light pollution. Further, most (>65%) of the very high‐ and high‐density nesting areas for each species/subpopulation, except for the Kemp's ridley, were exposed to coastal development. Forty‐nine nesting sites were selected as conservation hotspots; of those high‐density nesting sites, 49% were sites with no/low exposure to coastal development and the other 51% were exposed to high‐density coastal development. Conservation strategies need to account for ~66.8% of all marine turtle nesting areas being on private land and for nesting sites being exposed to large numbers of seasonal residents.